Visit‐to‐visit variability in albuminuria predicts renal function deterioration in patients with type 2 diabetes - Lin, Chih‐Hung; Lai, Ying‐Chuen; Chang, Tien‐Jyun; Jiang, Yi‐Der; Chang, Yi‐Cheng; Chuang, Lee‐Ming (Journal of diabetes investigation, 2022)
Aims/Introduction We aimed to study the predictive ability of visit‐to‐visit variability in albuminuria for changes in renal function in patients with type 2 diabetes mellitus. Materials and Methods The cohort study was carried out in a single medical center. In the model development cohort of 1008 subjects, we developed the albuminuria variability score (AVS) to evaluate the visit‐to‐visit variability in albuminuria, which was the percentage of the number of changes in the urine albumin : creatinine ratio ≥3.39 mg/mmol among all visit‐to‐visit urine albumin : creatinine ratio differences within an individual. Multivariate logistic regression was applied to predict the influence of AVS levels on the occurrence of study end‐points. In another independent validation cohort of 310 participants, survival analysis was carried out to evaluate the ability of AVS in predicting the study end‐point. Results In the model development cohort, a higher AVS was associated with higher adjusted odds of having a declined or rapidly declined estimated glomerular filtration rate (eGFR) trajectory (1.84, 95% confidence interval 1.23–2.76 and 5.70, 95% confidence interval 2.28–14.25, respectively), a resultant eGFR <60 mL/min/1.73 m2 (2.61, 95% confidence interval 1.63–4.16) and a >40% decline in eGFR from baseline (6.44, 95% confidence interval 2.15–19.26). In the validation cohort, a higher AVS independently predicted a 5‐year decrease of >40% in eGFR to <60 mL/min/1.73 m2 (adjusted hazard ratio 3.33, 95% confidence interval 1.10–10.05). Integrated discrimination index and concordance statistics showed that AVS significantly improved the predictive ability of the models. Conclusions Visit‐to‐visit variability in albuminuria can independently predict long‐term renal function deterioration in patients with type 2 diabetes mellitus. Further investigations are warranted to elucidate the potential clinical applications. The clinical importance of visit‐to‐visit variability in albuminuria is not clear. We developed a simple system named the albuminuria variability score to describe such variability. A high albuminuria variability score predicts 5‐year renal function deterioration in patients with type 2 diabetes.